Exploring the Properties of the Electron Strahl at 1 AU as an Indicator of the Quality of the Magnetic Connection Between the Earth and the Sun - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2021)
In this report some properties of the electron strahl at 1 AU are examined to assess the strahl at 272 eV as an indicator of the quality of the magnetic connection of the near-Earth solar wind to the Sun. The absence of a strahl has been taken to represent either a lack of magnetic connection to the corona or the strahl not surviving to 1 AU owing to scattering. Solar-energetic-electron (SEE) events can be used as indicators of good magnetic connection: examination of 216 impulsive SEE events finds that they are all characterized by strong strahls. The strahl intensity at 1 AU is statistically examined for various types of solar-wind plasma: it is found that the strahl is characteristically weak in sector-reversal-region plasma. In sector-reversal-region plasma and other slow wind, temporal changes in the strahl intensity at 1 AU are examined with 64 s resolution measurements and the statistical relationships of strahl changes to simultaneous plasma-property changes are established. The strahl-intensity changes are co-located with current sheets (directional discontinuities) with strong changes in the magnetic-field direction. The strahl-intensity changes at 1 AU are positively correlated with changes in the proton specific entropy, the proton temperature, and the magnetic-field strength; the strahl-intensity changes are anti-correlated with changes in the proton number density, the angle of the magnetic field with respect to the Parker-spiral direction, and the alpha-to-proton number-density ratio. Reductions in the strahl intensity are not consistent with expectations for a simple model of whistler-turbulence scattering. Reductions in the strahl intensity are mildly consistent with expectations for Coulomb scattering, however the strongest-observed plasma-change correlations are unrelated to Coulomb scattering and whistler scattering. The implications of the strahl-intensity-change analysis are that the change in the magnetic-field direction at a strahl change represents a change in the magnetic connection to the corona, resulting in a different strahl intensity and different plasma properties. An outstanding question is: Does an absence of an electron strahl represent a magnetic disconnection from the Sun or a poor strahl source in some region of the corona?